KONTROL STRUKTUR GEOLOGI TERHADAP ALTERASI DAN MINERALISASI BIJIH DAERAH HARGOSARI, KECAMATAN TIRTOMOYO, KABUPATEN WONOGIRI, PROVINSI JAWA TENGAH: STRUCTURAL CONTROLS ON ALTERATION AND ORE MINERALIZATION IN THE HARGOSARI AREA, TIRTOMOYO DISTRICT, WONOGIRI REGENCY, CENTRAL JAVA PROVINCE - Andi Faesal; Wahyu Hermansyah; Aji Syailendra Ubaidillah; Z.A Munarfan Putra; Iwan Dermawan; Khatib Syarbini; Heni Pujiastuti; Melinda Dwi Erintina; Dwi Winarti; Arief Rachman Hakim; Aryaumul Patriani (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2026)
This study evaluates the influence of geological structures on hydrothermal alteration and ore mineralization processes in the Hargosari area, Tirtomoyo District, Wonogiri Regency, Central Java. Detailed field mapping over an area of ±3 km², petrographic analysis, and structural interpretation using the Riedel shear model identify a principal mineralized zone extending approximately 1.2 km with a dominant orientation of N60°E. Mineralization is primarily controlled by strike-slip fault systems, consisting of dextral NW–SE and sinistral SW–NE faults that served as major conduits for hydrothermal fluid migration. These fluids produced quartz vein fragments and sulfide mineral assemblages dominated by pyrite, galena, sphalerite, and chalcopyrite. Secondary structures, including extensional fractures and en-echelon tension veins, developed within a transpressional regime, providing additional permeability pathways for mineralizing fluids. The Kayulawang Fault is interpreted as a pre- to syn-mineralization structure, while younger fractures represent post-mineralization deformation. Propylitic and argillic alteration zones envelop basaltic-andesitic lava bodies, reflecting multistage fluid–rock interactions associated with Plio–Pleistocene tectonic evolution. These findings underscore the critical role of strike-slip fault configuration and regional tectonic dynamics in controlling ore distribution and alteration patterns within volcanic-arc environments, offering important implications for regional mineral exploration strategies.